PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU KEJAHATAN DI DALAM PESAWAT UDARA DITINJAU BERDASARKAN KETENTUAN HUKUM PIDANA - Putra, Nofendri Pratama; Husna, Lenny (SCIENTIA JOURNAL, 2019)
As an archipelagic country, Indonesia has demands in terms of transportation facilities that are relatively faster, one of which is through air, which is necessity cannot be ignored. However, the growth of air transportation can also be misused by some people by violating the law. The purpose of this research is to find the term of accountability of criminal offenders in airplane based on the provisions of law criminal and also to know the policy of aviation crime in Indonesia. The study uses normative and analytical descriptive research methods. From this study the authors found that anyone in the airplane with the act unlawful appropriation or seize or retain control of aircraft in flight shall be imprisoned for twelve years in connection with Article 479l of the Criminal Code. The form of aviation crime in Indonesia through teh fixed procedure of securing air transport companies in accordance with Ministerial Decree KM.73 of 1996 concerning civil aviation security and also the implementation of passenger inspection procedures in accordance with the Director General of Civil Aviation SKEP/2765/XII/2010 which regulates procedures for checking passengers security.